1995
DOI: 10.1542/peds.95.2.210
|View full text |Cite
|
Sign up to set email alerts
|

Eating in Preschool Children With Cystic Fibrosis and Healthy Peers: Behavioral Analysis

Abstract: Study objective. To investigate calorie intake, behavioral eating styles, and parent perception of eating behavior of preschool children with cystic fibrosis (CF) compared with healthy peers. Design. A two group comparison study. Setting. A clinical sample of 32 preschool children with CF (aged 2 to 5 years) and a community sample of 29 healthy peers matched for age and socioeconomic status. Measurements and main results. The two groups did not differ on the total n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 86 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…It is also noteworthy that despite the increased calorie intake in school-age versus preschool-age children with CF, the school-age children in this sample achieved a lower percent ideal body weight (87.3%) (Stark et al, 1997) than the preschool sample (98.5%) (Stark et al, 1995). In addition, whereas the preschool-age children with CF did not differ from their same-age peers on absolute height and weight (Stark et al, 1995), the school-age sample of children with CF were found to be significantly shorter than same-age peers and to weigh significantly less (Stark et al, 1997).…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…It is also noteworthy that despite the increased calorie intake in school-age versus preschool-age children with CF, the school-age children in this sample achieved a lower percent ideal body weight (87.3%) (Stark et al, 1997) than the preschool sample (98.5%) (Stark et al, 1995). In addition, whereas the preschool-age children with CF did not differ from their same-age peers on absolute height and weight (Stark et al, 1995), the school-age sample of children with CF were found to be significantly shorter than same-age peers and to weigh significantly less (Stark et al, 1997).…”
Section: Discussionmentioning
confidence: 86%
“…It is also noteworthy that despite the increased calorie intake in school-age versus preschool-age children with CF, the school-age children in this sample achieved a lower percent ideal body weight (87.3%) (Stark et al, 1997) than the preschool sample (98.5%) (Stark et al, 1995). In addition, whereas the preschool-age children with CF did not differ from their same-age peers on absolute height and weight (Stark et al, 1995), the school-age sample of children with CF were found to be significantly shorter than same-age peers and to weigh significantly less (Stark et al, 1997). The trend for children with CF to decline in weight percentile as they age is seen in the national data collected by the CF Foundation (Cystic Fibrosis Foundation, 2003) and longitudinal studies of children with CF, and suggests that despite increased caloric intake, school-age children still are at significant risk, and possibly greater risk, because of their growth status (Zemel, Jawad, Fitzsimmons, & Stallings, 2000).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations